Realitas Kesehatan Ibu Nifas dalam Perspektif Ontologi: Studi Kualitatif Literatur tentang Pengalaman Pemulihan Pasca Persalinan - Sitti Aisyah Ansi; Suryo Ediyono (Universitas Pahlawan Tuanku Tambusai, 2026)
The postpartum period is a critical phase in maternal health that is often understood primarily as a biological recovery process following childbirth. However, a mother’s health experience during this period is actually more complex, as it involves physical, psychological, and social changes, as well as women’s subjective interpretations of their bodies and lives. Therefore, a more holistic approach is needed to understand the realities of postpartum maternal health. This study aims to analyze the reality of postpartum maternal health from an ontological perspective by examining how the experience of postpartum recovery is understood as a multidimensional phenomenon. The study employs a qualitative approach using library research (literature review) through the analysis of various scientific literature addressing maternal health, postpartum experiences, and the philosophy of health. The literature was obtained from academic databases and analyzed using thematic content analysis to identify key themes related to postpartum maternal health experiences. The results indicate that postpartum maternal health is not only related to the body’s biological condition but also involves women’s subjective experiences and is influenced by social and cultural contexts. This study concludes that postpartum maternal health must be understood as a holistic reality encompassing biological, psychological, and social dimensions, as well as the existential meaning women experience after childbirth.